The effect of knowledge, species aesthetic appeal, familiarity and conservation need on willingness to donate. (4th January 2019) - Lundberg, P.; Vainio, A.; MacMillan, D. C.; Smith, R. J.; Veríssimo, D.; Arponen, A.
Abstract: Environmental non‐governmental organizations (ENGOs) largely select flagship species for conservation marketing based on their aesthetic appeal. However, little is known about the fundraising effectiveness of this approach or how it compares to ecosystem conservation campaigns that use habitat types as flagships. By performing a willingness to donate (WTD) survey of potential online donors from Finland, we identified which motivations and donor characteristics influence their preferences for a range of different flagship species and ecosystems. Using the contingent valuation method and the payment card approach, we found the combined funding for eight mammal flagship species was 29% higher funding than for eight bird flagship species. Furthermore, the aesthetically more appealing species, as well as the species and ecosystems that are native to Finland, attracted the most funding. We then used ordinal logistic regression to identify the factors influencing a donor's WTD, finding that knowledge of biodiversity conservation and familiarity with the flagship was associated with an increased WTD to birds and ecosystems, and people with higher education levels had an increased WTD to ecosystems. Surprisingly, species aesthetic appeal was not related to an increased WTD, although "need of conservation" was, suggesting that highlighting the plight of these less appealing threatened species or ecosystems could raise money. Our results suggest that the factors driving donating to mammals, birds or ecosystems differ, and so underline the importance of considering the diverse motivations behind donation behaviour in fundraising campaigns. They also provide new evidence of the motivations of online donors, an under‐studied group who are likely to become an increasingly important source of conservation funding. Abstract : Flagship species that are used to promote conservation projects and to induce donations are often chosen based on their aesthetic appeal, but donors may have also other preferences. In addition, it is not clear what motivates donors to choose between species and habitat level campaigns, and in order to enhance the effectiveness of conservation campaigns we need more knowledge on the drivers behind donating behaviour. From conservation marketing perspective, we compared how different factors, such as species aesthetic appeal, familiarity and conservation need as well as donor characteristics influence donating to the conservation of flagship species and their ecosystems among potential online donors. Our results shed light on the preferences of this unexplored but increasingly important donor segment, and suggest that factors driving donating to mammals, birds and ecosystems differ, at least online.